Office building typologies and circadian potential - Figueiredo, Erika Ciconelli de; Pisani, Maria Augusta Justi (ENCONTRO NACIONAL DE CONFORTO NO AMBIENTE CONSTRUÍDO, 2023)
Circadian rhythms are internal manifestations of the solar day that allow adaptations to environmental-temporal changes. Mood disorders are often associated with disrupted circadian clock-controlled responses, whereas circadian rhythm disruption is correlated to jet lag, night-shift work, or to exposure to artificial light at night. Modern lifestyle patterns lead to circadian rhythm disruption, and it results in several diseases. Circadian rhythm disruption is one of the factors most often investigated, besides smoking, diet, fatigue and quality sleep, increased body mass index and obesity. Lack of enough daylight at daytime and the exposure to electric light at nighttime can disconnect people from the natural environment and lead to psychological issues. The aims of the current research are to analyze the circadian potential of three building models based on WELL Certification, to compare their performance, and to draw design guidelines about circadian rhythm and users’ well-being to be applied to office buildings in São Paulo City, São Paulo State, Brazil. Adaptive Lighting for Alertness (ALFA tool) was used to calculate the Equivalent Melanopic Lux for WELL Certification criteria in the investigated scenarios. Results have indicated that shallow office plans can benefit users by providing them with regular circadian rhythm o help improving their sleep quality, reducing their stress and preventing severe diseases.